2022
DOI: 10.7150/ijms.76013
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis in patients with asthma after inhaled combination therapy with long-acting β2-agonists and corticosteroids

Abstract: Introduction: Asthma is one of the major public health problems that imposes a great burden on societal, financial, and healthcare around the world. Asthma poorly affects the health-related quality of life and daily activities of patients. Treatment of asthma, including inhaled corticosteroids (ICS) and long-acting beta-agonists (LABAs), mainly aims to improve the lung function and reduce symptoms and exacerbations. Current treatment regimens are symptom-based strategies, and the status of airway inflammation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Liang et al reported ICS/LABAs treatment reduced airway inflammation and remodeling, but did not completely suppress allergic stimulation related pathways in treated patients. IgE levels after treatment also showed a decreasing trend, but without statistical significance 58 . However, our target predicted mRNA, IL-4, IL-10, and FCER2, were not reported in this RNA transcription study.…”
Section: Discussionmentioning
confidence: 92%
“…Liang et al reported ICS/LABAs treatment reduced airway inflammation and remodeling, but did not completely suppress allergic stimulation related pathways in treated patients. IgE levels after treatment also showed a decreasing trend, but without statistical significance 58 . However, our target predicted mRNA, IL-4, IL-10, and FCER2, were not reported in this RNA transcription study.…”
Section: Discussionmentioning
confidence: 92%
“…The use of Inhaled Corticosteroids/ Long-Acting Beta2 Agonists (ICS/LABAs) is known to reduce airway inflammatory and remodeling pathways. For instance, in post-ICS-LABA treatment, there's a noted downregulation in the expression of various elements like nuclear receptor transcription coactivator, N-acetyltransferase, protein tyrosine kinase, nuclear receptor, and RNA polymerase II-activating transcription factor [158].…”
Section: The Role Of Standard Therapy In Airway Remodeling (Lama)mentioning
confidence: 99%
“…The use of Inhaled Corticosteroids/Long-Acting Beta2 Agonists (ICS/LABAs) is known to reduce airway inflammatory and remodeling pathways. For instance, in post-ICS-LABA treatment, a noted downregulation has been reported in the expression of various elements like nuclear receptor transcription coactivator, N-acetyltransferase, protein tyrosine kinase, nuclear receptor, and RNA polymerase II-activating transcription factor [ 157 ].…”
Section: Relevant Therapeutic Options and New Potential Therapeutic T...mentioning
confidence: 99%